Emission characteristics of using different alternative fuels with petroleum diesel in a compression ignition (ci) engine - Liaquat, A.M.; Kalam, M.A.; Masjuki, Haji Hassan; Rezza, A. (2010)
Stringent emission norms and depletion of oil resources have led the researchers to find alternative fuels for internal combustion engines. The main objectives of this study are to investigate the effects of using different types of fuel samples interns of emission characteristics and feasibility of using alternative fuels. Therefore, in this study five fuel samples (FSs) such as: 100% diesel fuel (FS1); 5% palm diesel and 95% diesel fuel (FS2); 5% jatropha oil and 95% diesel fuel (FS3); 5% jatropha oil, 5% palm diesel and 90% diesel fuel (FS4); and 10% jatropha oil, 10% palm diesel and 80% diesel fuel (FS5) respectively were used to analyze the exhaust emissions which are included carbon monoxide, carbon dioxide, nitrogen oxide and also exhaust gas temperature. All tests were carried out on a single cylinder DI YANMAR engine model YF120-M at constant speed of 2000 rpm at varied load conditions between 5 Nm and 17.5 Nm with intervals of 2.5 Nm. The results presented in this study showed that the FS2 and FS3 have a potential to reduce emissions compared to diesel fuel (FS1). Therefore, in conclusion the FS2 and FS3 can be feasible alternative fuels for the CI diesel engine without any engine modification.